The Role of Teachers in Teaching Children Who Have Symptoms of Hyperactive Behavior in Group B of the TK Yayasan Perguruan Gajah Mada Medan Timur - Jesika Simanjuntak; Sariana Marbun (PT FORMOSA CENDEKIA GLOBAL, 2023)
The purpose of this study was to determine the teacher's role in teaching children who have symptoms of hyperactive behavior in group B TK Gajah Mada College Foundation, Medan Timur. The method in this study was qualitative using observation, observation and interview methods which consisted of two focuses, namely the role of the teacher and the behavioral symptoms of hyperactive children. Data was collected through observation, interviews, and documentation and then analyzed using interactive analysis techniques, namely data reduction, data presentation, and drawing conclusions. The results showed that there were three children who tended to show signs of hyperactive behavior and the teacher performed his role as an educator by getting closer to the child so that the teacher could understand the child's personality and behavior. As an educator guiding and fostering children's behavior by providing reinforcement and punishment to children. Furthermore, as an educator fostering children's character by providing training, improvement and feedback. As a facilitator by providing tools, media, and games needed by children to increase interest in learning and children's needs. The teacher conveys media presentations through stories and dialogues. As a dynamist by creating a conducive learning atmosphere and environment so that children feel comfortable and safe during the learning process. So to create a comfortable classroom atmosphere, as a dynamic teacher, the teacher creates classrooms and a good school environment for children's growth.